Study of Structural, Dielectric, and Phase Transition of Strontium Doped BaTiO3 - Zouitine, Asmaa; Ghandouri, Abdelhak El; Elbasset, Abdelhalim; Abdi, Farid; Lamcharfi, Taj-dine; Laribou, Hicham; Mrharrab, Lamiae; Mohammed, Zouhairi (Universitas Gadjah Mada, 2025)
In this paper, we studied the effect of strontium doping on the structural, microstructural, dielectric, and electrical properties of Ba1-xSrxTiO3 (BSxT) ceramics prepared via the sol-gel method, with x = 0.00 to 0.15. The results obtained from the X-ray diffraction spectrum confirmed the creation of the pure perovskite structure, with the diffraction peaks of the BSxT shifting toward the bigger 2θ with increasing Sr content. Scanning electron microscopy images show that the grain size of the BSxT ceramics decreases with increasing Sr content. An increase in Sr content appears to lower the activation energy by the factor of 0.16 meV/mol% and to decrease Curie temperature by the factor of 3.34 °C/mol%. Furthermore, in case of 15 mol% of Sr addition, the dielectric constant value is increased about twice. Moreover, the relationship between grain sizes and dielectric properties was also investigated. Using the frequency measurement method (up to 2 MHz in a step of 1 kHz), we are able to determine the temperature of transition without using the conventional method.